SOCS3 as a potential driver of lung metastasis in colon cancer patients - Li, Xuejie; Yang, Zuyi; Chen, Bi; Gu, Lei; Tian, Guoyan; Sui, Xinbing (Frontiers in Immunology, 2023)
Background: The suppressor of cytokine signaling 3 (SOCS3) is the negative feedback regulator of the JAK-STAT signaling pathway. The purpose of our study was to investigate the SOCS3 status in colon primary tumor and lung metastasis and its relationship with macrophages. Methods: The SOCS3 expression pattern and its relationship with the immune response in pan-cancer was investigated using multiple methods. Samples and corresponding clinical information of 32 colon cancer patients with lung metastasis were collected, and the CD68, CD163, and SOCS3 status were conducted using immunohistochemistry (IHC). The relationship between SOCS3 status and macrophage markers was analyzed. Besides, we explored the molecular mechanisms of SOCS3 in lung metastasis via the TCGA database. Results: High SOCS3 expression was more inclined to poor prognosis and was positively correlated with main immune cell infiltration in almost each cancer type, especially in colon cancer. Compared with the colon primary tumor, lung metastasis harbored higher CD163 and SOCS3 expression, and high SOCS3 expression was more likely to be associated with high CD163 expression in lung metastasis. Besides, the exceptional differentially expressed genes in lung metastasis significantly enriched in immune responses and regulations. Conclusions: SOCS3 possessed value as a prognostic marker and target for immunotherapeutic intervention in different tumors and might be a potential target of tumor progression and tumor immunotherapy in colon cancer.